Functional Strength Training and Movement Performance Therapy for Upper Limb Recovery Early Poststroke—Efficacy, Neural Correlates, Predictive Markers, and Cost-Effectiveness: FAST-INdiCATE Trial - Hunter, Susan M.; Johansen-Berg, Heidi; Ward, Nick; Kennedy, Niamh C.; Chandler, Elizabeth; Weir, Christopher John; Rothwell, John; Wing, Alan M.; Grey, Michael J.; Barton, Garry; Leavey, Nick Malachy; Havis, Claire; et al. (Frontiers in Neurology, 2018)
Background: Variation in physiological deficits underlying upper limb paresis after stroke could influence how people recover and to which physical therapy they best respond. Objectives: To determine whether functional strength training (FST) improves upper limb recovery more than movement performance therapy (MPT). To identify: (a) neural correlates of response, and (b) whether pre-intervention neural characteristics predict response. Design: Explanatory investigations within a randomised, controlled, observer-blind, multi-centre trial. Randomization was computer-generated and concealed by an independent facility until baseline measures were completed. Primary time point was outcome, after the six-week intervention phase. Follow-up was at six months after stroke. Participants: with some voluntary muscle contraction in the paretic upper limb, not full dexterity, when recruited up to 60 days after an anterior cerebral circulation territory stroke. Interventions: conventional physical therapy (CPT) plus either MPT or FST for up to 90 minutes-a-day, five days-a-week for six weeks. FST was “hands-off” progressive resistive exercise cemented into functional task training. MPT was “hands-on” sensory/facilitation techniques for smooth and accurate movement. Outcomes: The primary efficacy measure was the Action Research Arm Test (ARAT). Neural measures: fractional anisotropy (FA) corpus callosum midline; asymmetry of corticospinal tracts FA; and resting motor threshold of motor evoked potentials. Analysis: of covariance models tested ARAT change from baseline. At outcome: correlation coefficients assessed relationship between change in ARAT and neural measures; an interaction term assessed whether baseline neural characteristics predicted response. Results: 288 participants had: mean age of 72.2 (standard deviation 12.5) years and mean ARAT 25.5 (18.2). For 240 participants with ARAT at baseline and outcome the mean change was 9.70 (11.72) for FST+CPT; and 7.90 (9.18) for MPT+CPTwhich did not differ statistically (p=0.298). Correlations between ARAT change scores and baseline neural values were between 0.199, p=0.320, for MPT+CPT resting motor threshold (n=27) and -0.147, p=0.385, for asymmetry of corticospinal tracts FA (n=37). Interaction effects between neural values and ARAT change between baseline and outcome were not statistically significant. Conclusions: There was no significant difference in upper limb improvement between FST and MPT. Baseline neural measures did not correlate with upper limb recovery or predict therapy response.